EVALUASI NUMERIK METODE PENGGALIAN TEROWONGAN CISUMDAWU - I Gde Budi Indrawan; Ridwan Umbara; Fahmi Aldiamar (Jurnal Jalan-Jembatan, 2019)
This paper presents results of research works carried out to evaluate the excavation method of the left (west) side of the Cisumdawu Tunnel by a numerical method. Using data obtained from site investigation during design process and face mapping at eight observation points, tunnel excavations by bench cut (multiple), full face with bench cut, and centre diaphragm methods were numerically modelled in two dimension using a finite element method. The numerical modelling results were compared with field measurement results to determine the most suitable excavation method applied in Cisumdawu Tunnel. Results of this research showed that roof displacements induced by the bench cut (multiple) excavation method obtained in the numerical modelling was close to that obtained in the field measurement. The bench cut (multiple) excavation method applied in the field induced lower roof displacement value than the full face with bench cut and centre diaphragm methods. However, the three excavation methods induced roof displacements lower than a 10 cm maximum displacement specified in the JSCE (2007) and roof strength factor > 1.25, indicating stable tunnel condition.